Methodological challenges faced in doing research with vulnerable women: reflections from fieldwork experiences - Jackson, Margot; Thummapol, Onouma; Park, Tanya; Barton, Sylvia (My University, 2019)
Methodological challenges of qualitative research involving people considered vulnerable are widely prevalent, for which many novice researchers are not well equipped or prepared for. This places great physical and emotional demands on the researchers. However, a discussion to bring to light the issues related to the researchers’ experiences and practical concerns in the field remains largely invisible in the literature. This article presents the reflective accounts of a doctoral researcher’s fieldwork experience, particularly in relation to the methodological challenges encountered in carrying out research with vulnerable women in rural and northern Thailand. Four of these challenges pertain to selecting a field site and acquiring access, recruiting and building trust, maintaining privacy and confidentiality, and being vulnerable as a researcher. Suggestions from the literature and practical strategies the researcher employed to deal with such challenges and real dilemmas are discussed. This article calls for more formal safeguards during the research process and suggests that researchers reflect upon their experiences and emotions in undertaking a field research, making the accounts of their research journey heard and beneficial to other novice and/or experienced researchers.
Keywords: focused ethnography; community-based research; methods in qualitative inquiry; narrative; ethnography